1988
DOI: 10.1093/protein/2.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Use of site-directed mutagenesis to probe the role of Cys149 in the formation of charge-transfer transition in glyceraldehyde-3-phosphate dehydrogenase

Abstract: Oligonucleotide-directed mutagenesis was employed to produce mutants of the glyceraldehyde-3-phosphate dehydrogenase (GAPDH) of Escherichia coli and Bacillus stearothermophilus. Three different mutants proteins--His176----Asn, Cys149----Ser, Cys149----Gly--were isolated from one or both of the enzymes. The study of the properties of these mutants has shown that Cys149 is clearly responsible for the information of a charge-transfer transition, named the Racker band, observed during the NAD+ binding to apoGAPDH.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…strain PCC 6803 has been analyzed and found to have the structural features typical of other gap genes, including (i) the well-conserved sequence of the active site 152 ASCTTNCL 159 (according to the numbering of the predicted Synechocystis sp. strain PCC 6803 GAPDH2) around the C 154 (in boldface) that forms the thioester bond with the substrate in the catalysis (30) and (ii) the so-called S-loop region (residues 183 to 205) which is involved in the interaction between subunits and the binding of the nucleotide cofactor and displayed prokaryotic signatures (16). A proline residue of this region present in glycolytic GAPDHs, P 188 according to the numbering of Bacillus stearothermophilus GAPDH (5), has been postulated to be involved in pyridine nucleotide cofactor specificity conferring absolute specificity for NAD (12).…”
Section: Resultsmentioning
confidence: 99%
“…strain PCC 6803 has been analyzed and found to have the structural features typical of other gap genes, including (i) the well-conserved sequence of the active site 152 ASCTTNCL 159 (according to the numbering of the predicted Synechocystis sp. strain PCC 6803 GAPDH2) around the C 154 (in boldface) that forms the thioester bond with the substrate in the catalysis (30) and (ii) the so-called S-loop region (residues 183 to 205) which is involved in the interaction between subunits and the binding of the nucleotide cofactor and displayed prokaryotic signatures (16). A proline residue of this region present in glycolytic GAPDHs, P 188 according to the numbering of Bacillus stearothermophilus GAPDH (5), has been postulated to be involved in pyridine nucleotide cofactor specificity conferring absolute specificity for NAD (12).…”
Section: Resultsmentioning
confidence: 99%
“…This is a situation similar to that observed with phosphorylating NAD-dependent glyceraldehyde-3-phosphate dehydrogenase. In this latter enzyme, it was shown that the transition was due to a charge transfer between the essential Cys-149 and the nicotinamide ring of the cofactor acting as an electron donor and electron acceptor, respectively (20,21). Therefore, it was reasonable to hypothesize that Ab 333 was due to a charge transfer between Cys-302 and the nicotinamide of NADP.…”
mentioning
confidence: 98%
“…These strains were transformed with the plasmid pBS::EcogapA. This plasmid was constructed by cutting out the HindIII-BamHI 2,149-nucleotide fragment from phage M13mp9:EcogapA (38) and inserting it into plasmid BSIISK+ (Stratagene). The plasmid pBS::EcogapA contains the entire gapA gene with a 346-nucleotide upstream flanking region.…”
mentioning
confidence: 99%